2015
DOI: 10.1590/s1517-838246420140024
|View full text |Cite
|
Sign up to set email alerts
|

Screening and characterization of endophytic Bacillus and Paenibacillus strains from medicinal plant Lonicera japonica for use as potential plant growth promoters

Abstract: A total of 48 endophytic bacteria were isolated from surface-sterilized tissues of the medicinal plant Lonicera japonica, which is grown in eastern China; six strains were selected for further study based on their potential ability to promote plant growth in vitro (siderophore and indoleacetic acid production). The bacteria were characterized by phylogenetically analyzing their 16S rRNA gene similarity, by examining their effect on the mycelial development of pathogenic fungi, by testing their potential plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(67 citation statements)
references
References 38 publications
4
60
0
3
Order By: Relevance
“…SSRN1 MF105749 shared a common ancestor with Pseudomonas taiwanensis KM576802 isolated from rhizosphere soil with 91% bootstrap value. All current bacterial endophytes strains were reported as endophytes from various plant species (Chaudhry and Patil, 2013;Christina et al, 2013;Mahummad et al, 2014;Zhao et al, 2015). Similar studies on isolation of endophytes have been reported by other researchers, …”
Section: Phylogenetic Relationshipsupporting
confidence: 55%
“…SSRN1 MF105749 shared a common ancestor with Pseudomonas taiwanensis KM576802 isolated from rhizosphere soil with 91% bootstrap value. All current bacterial endophytes strains were reported as endophytes from various plant species (Chaudhry and Patil, 2013;Christina et al, 2013;Mahummad et al, 2014;Zhao et al, 2015). Similar studies on isolation of endophytes have been reported by other researchers, …”
Section: Phylogenetic Relationshipsupporting
confidence: 55%
“…do not cause any visible damage or morphological alterations to the host. Therefore, these bacteria can be beneficial for the survival of the host species against environmental stresses and microbial competition 6, 7 . Furthermore, these bacteria may promote the growth of the plant through the formation of nodules with non-specific hosts 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Screening, production, and optimization of L‐asparaginase from this bacterium have been studied . Endophytic P. polymyxa has been isolated from medicinal plant Lonicera japonica . This plant has been used in herbal medicine due to its anticancer effects on the respiratory system .…”
Section: Resultsmentioning
confidence: 99%
“…48 Endophytic P. polymyxa has been isolated from medicinal plant Lonicera japonica. 49 This plant has been used in herbal medicine due to its anticancer effects on the respiratory system. 50 Moreover, isolation of this bacterium from Ginseng (Panax ginseng CA Meyer), a well-known anticancer medicinal plant, has been reported.…”
Section: Sequence Retrievalmentioning
confidence: 99%